Community Service Program on the Implementation of Ergonomic Work Postures among Processed Food Workers to Reduce Muscle Fatigue - Lutfi, Lutfi Ani; lemadi, gayuh; emra, devianita; lombardo, doddy (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the food sector play a vital role in supporting local economic growth, job creation, and the preservation of traditional culinary practices. However, issues related to occupational health and safety, particularly muscle fatigue caused by non-ergonomic working postures, remain inadequately addressed. This Community Service Program (PKM) was conducted at Belfii MSME, South Tangerang, involving 15 respondents. Data were collected through interviews, direct observations, questionnaires, and posture assessment using the Rapid Entire Body Assessment (REBA) method. Findings revealed that most workers experienced muscle fatigue in the waist, back, legs, and arms. REBA assessment indicated very high-risk levels, particularly during activities of lifting and lowering materials in the raw material warehouse, with a score of 14, requiring immediate corrective actions. Ergonomic interventions were implemented through awareness sessions and demonstrations on proper working postures, including squatting techniques when lifting materials, the use of worktables to minimize bending, and maintaining upright postures while lowering loads. Post-intervention evaluations showed reduced musculoskeletal complaints and increased worker awareness of ergonomics. The application of ergonomic principles was proven effective in minimizing physical strain, improving comfort, and enhancing productivity. This program recommends designing simple work aids, reorganizing workstations, and providing regular ergonomic training for sustainable improvements.